Pengaruh Pupuk Organik Limbah Biogas Kotoran Sapi Terhadap Pertumbuhan Dan Produksi Tanaman Cabai Merah Keriting (Capsicum annum var. Longum) - Ajang Maruapey (Agrologia, 2017)
This study aims to determine the effect of organic fertilizer waste biogas cow dung on the growth and production of red curly chili plants. The experiment was carried out at Mariyat Village Farmer Land, Mariat District, Sorong District, from August to October 2016. The experiment used 4 treatment of organic fertilizer of cow dung biogas waste with dosage 0, 6, 9, 12 kg / plot, designed using random block design with repeated three times. The results showed that, the application of organic fertilizer biogas waste cow dung affect the plant height, the number of productive branches, the age of flowering, the number of fruit, fruit length, fruit weight per plant and the production of red curly pepper plants. Giving at a dose of 12 kg per plot gives a better effect than with a lower dose.